Discrimination and Sleep Mediate Ethnic/Racial Identity and Adolescent Adjustment: Uncovering Change Processes With Slope‐as‐Mediator Mediation. Issue 3 (17th July 2019) - Yip, Tiffany; Cham, Heining; Wang, Yijie; El‐Sheikh, Mona
Abstract : This study employs slope‐as‐mediator techniques to explore how the daily association between ethnic/racial discrimination and sleep disturbances serves as an intermediary link between ethnic/racial identity (ERI) and psychological adjustment. In a diverse sample of 264 adolescents ( M age = 14.3 years old, 70% female, 76% United States born, 25% African American, 32% Asian American, 43% Latinx), discrimination was associated with sleep disturbance. Furthermore, ERI commitment buffered the impact of discrimination on sleep, whereas ERI exploration exacerbated the impact of discrimination. Finally, the daily level association between discrimination and sleep (i.e., daily slope) mediated the association between ERI and adolescent adjustment. Substantive links between discrimination and sleep are discussed as well as broader applications of slope‐as‐mediator techniques.